A purposeful lifestyle is a healthful lifestyle: Linking sense of purpose to self-rated health through multiple health behaviors. (September 2019) - Hill, Patrick L; Edmonds, Grant W; Hampson, Sarah E
Having a purpose in life has been consistently linked to subjective and objective health markers. Using data from the Hawaii Study of Personality and Health ( n  = 749, Mage  = 60.1 years), we tested multiple health behaviors as unique mediators of the correlation between sense of purpose and self-rated health ( r  = .29). Correlational analyses found that participants' sense of purpose was positively associated with their reports of vigorous and moderate activity, vegetable intake, flossing, and sleep quality. Combined in a multiple-mediator model, bootstrapping analyses suggested that sleep quality and vigorous activity proved significant unique mediators.